Intervening Role Quality Online System in Relationship Between Implementation Inaportnet and Effectiveness Ship Clearance In-Out - Nofrisel Nofrisel; Kintan Litania Kirani; Aulia Rizki Indriyanti; Rahmat Hidayat (Dinasti Review, 2025)
Recently trend of port management focus on fast and accurate services. Indonesian port applies Inaportnet system to accelerate ship clearance in-out. Obstacles in application are often encountered, such as lack of skill and difficulties data integration on systems. This study aims to test the mediating function quality online system in identifying variables affecting Inaportnet application. This study uses quantitative techniques and saturated sample of 110 respondents from all staff of Pertamina Trans Kontinental Company, a company with strategic role managing transportation and energy logistics in Indonesia. The analysis employed the SEM-PLS method using SmartPLS 4 application to determine how strong the role of quality online system as a mediating variable. The results showed that quality online system and inaportnet implementation significantly impact with p-values of 0.000 and 0.001, increasing process effectiveness ship clearance in-out by 62%. This confirms the importance of quality online systems and optimal Inaportnet implementation for effectiveness ship clearance